Primary epithelial splenic cyst: A rare encounter - Pooja Sharma Kala; Sheenam Azad; Trisha Sharma; Seema Acharya (Wolters Kluwer Medknow Publications, 2019)
Splenic cysts are rare with an overall incidence of 0.07% in a large autopsy series and 0.5% among all the splenectomies done. The parasitic splenic cysts, usually caused by Echinococcus granulosus, account for 60% of all primary splenic cysts. The primary epithelial cysts account for 10% of all splenic cysts. We report a case of 30-year-old female presenting with left upper abdominal pain and heaviness. Computed tomography revealed a multiloculated cyst in spleen. Hydatid serology was negative. Total splenectomy was done. Histopathological evaluation was done and a diagnosis of primary epithelial splenic cyst was given.